PENGARUH PENAMBAHAN ZAT ADITIF ALAMI PADA BENSIN TERHADAP PRESTASI SEPEDA MOTOR 4-LANGKAH - Saputra, Wahyu Eko; Burhanuddin, Harmen; Susila, M.Dyan (FT UNILA, 2013)
The quality fuel affects combustion because the fuel quality will get better combustion. Therefore, it is necessary to improve the quality of the fuel to produce combustion. Such an increase in the octane rating of the fuel can result in increased good quality of the fuel. One method used is the addition of natural additives in the fuel. Tests were performed using a motorcycle test engine 100 cc 4-stroke is running test (road test and acceleration), and stationary testing. The test road test conducted by a distance of 10 km with an average speed of 50 km / h test aims to get the value of fuel consumption. Furthermore, using the acceleration test speed 0-80 km / h and 40-80 km / h which aims to get the fastest acceleration time. Then the stationary testing done on rotation 1.000 rpm and 3.000 rpm with a 5-minute aims to get the value of fuel consumption at rest. This test uses a natural variation in the dose of the gasoline additive used is 1:4, 1:6, 1:8, and 1:10. On testing fuel consumption with the distance 10 km can be seen that the concentration of 1:6 is the best concentration that can reduce fuel consumption by 23,31% (136 ml), compared with natural gasoline without additives (177,333 ml). Average time acceleration 0-80 km / h resulted in the concentration of the best natural additives 1:4 that is with an average acceleration of 10,847 seconds (20,69%). In testing acceleration 40-80 km / h obtained for the concentration of 1:8 with an average acceleration of 6,993 seconds (21,83%). Tests of stationary fuel consumption at 1,000 rpm for 5 minutes in to the best performance at a concentration of 1:8 that is 33,91% (12,667 ml) whereas at 3.000 rpm stationary best performance is obtained at a concentration of 1:10 30,71% (14,334 ml).Keywords : fuel, natural additives, engine performance.